Perbandingan Polimer pada Tablet Bukal dan Pengaruhnya pada Penghantaran - Muhammad Fathur Rahman; Rakha Widyastama; Padma Azzahra Ramadhani; Elita rahmah; Zalmi, Zalmiati; Nor Latifah (Jurnal Riset Farmasi, 2024)
Abstract.The development of mucoadhesive buccal films has become a focus of pharmaceutical research to improve oral drug delivery. The combination of polymers such as carbopol and HPMC improves film adhesion, while variations in excipients influence physical properties and drug release. The ideal film should be flexible, have a neutral pH, and be able to release the drug in a controlled manner. Although progress has been made, further research is needed for in vivo evaluation and addressing challenges such as interindividual variability. With great potential, mucoadhesive buccal films can be an attractive alternative for oral drug delivery. Abstrak. Pengembangan film bukal mukoadhesif menjadi fokus penelitian farmasi untuk meningkatkan penghantaran obat oral. Kombinasi polimer seperti karbopol dan HPMC meningkatkan adhesi film, sedangkan variasi eksipien memengaruhi sifat fisik dan pelepasan obat. Film yang ideal harus fleksibel, memiliki pH netral, dan dapat melepaskan obat secara terkontrol. Meskipun kemajuan telah dicapai, penelitian lebih lanjut diperlukan untuk evaluasi in vivo dan mengatasi tantangan seperti variabilitas antar individu. Dengan potensi yang besar, film bukal mukoadhesif dapat menjadi alternatif menarik untuk penghantaran obat oral.